An investigation into the factors influencing the cyclic behaviour of buckling‐restrained steel plate shear walls. Issue 1 (2nd September 2020) - Munesi, Ali; Sharbatdar, Mohammadkazem; Gholhaki, Majid
Abstract: Steel plate shear walls (SPSW) are being increasingly used in steel or concrete structures as lateral load‐resisting systems. Shear buckling is one of the major shortcomings of the SPSW and so to address this issue, buckling‐restrained steel plate shear walls (BRSPSW) have started to appear. Owing to the novel concept of this structural system, this paper aims to investigate the effect of factors influencing the response of BRSPSWs. For this purpose, a parametric study was conducted using ABAQUS software. Based on the results acquired from the hysteretic curves, an increase in the concrete compressive strength does not markedly affect the ductility and energy dissipation capacity. Moreover, it was observed that as the width of the gap between concrete panel and steel plate grows, the energy dissipation and response modification factor are reduced. Besides, the results indicate that as steel strength increases, so energy dissipation increases from 0.7 to 11.7 %. Accordingly, based on a comparison between the rate of improvement in shear capacity arising from an increase in the strength of the concrete panels, frame and steel plate, it is concluded that it would be much more rational to increase the concrete strength so that a high shear capacity can be achieved for the BRSPSW. Lastly, in all models, as the gap width increases from 0 to 20 mm and 20 to 35 mm, ductility decreases by 41 and 30 % respectively.